Incidence of Characteristic Findings during Veterinary Carcass Inspections 2010-2019 in the Czech Republic and the Relation to the Level of Health and Welfare of Individual Classes of Cattle - Kaluza, Michal; Vecerek, Vladimir; Voslarova, Eva; Semerad, Zbynek; Passantino, Annamaria (Animals, 2021)
Pathological findings in individual classes of cattle were assessed from the viewpoint of their localization and category. The objective of the study was to evaluate whether there are differences in the range and number of findings made between the individual classes of cattle. The results of veterinary inspections on 2,514,666 head of cattle slaughtered in the Czech Republic in the period 2010-2019 were used for the assessment. In terms of localization, the most frequent findings in cows were in the liver and pancreas (46.13%), the urinary tract (40.76%) and the lungs (36.23%). These findings also predominated in heifers and bulls, though they were recorded at lower frequencies (p < 0.01) than in cows. The most frequent pathological changes in heifers and bulls were chronic findings in the lungs (16.09% and 12.27%, respectively). The range of findings in calves differed significantly from other classes of cattle, primarily as the result of respiratory and diarrheal syndrome being the most frequent diseases in calves. Calves were the class of cattle most frequently diagnosed with findings in the lungs (44.89%), as well as other unclassified changes (24.43%) and overall changes (21.55%), which point to a systemic disorder of the organism. The results of this study confirmed the differing states of health in the individual classes of cattle and the differing health issues to which treatment and the prevention of the most frequently occurring infectious and non-infectious diseases must be adapted. Cattle welfare is affected not only by the level of health but also by the herd management and economics. This is confirmed by the range of findings, and the deterioration of living conditions especially in cows, likely because of great intensity of farming, but also in calves which suffered from emaciation or stunted growth.
Keywords: slaughter; pathological findings; welfare; veterinary inspection; health